Kinetics evaluation and thermal decomposition characteristics of co-pyrolysis of municipal sewage sludge and hazelnut shell. (January 2018) - Zhao, Bing; Xu, Xinyang; Li, Haibo; Chen, Xi; Zeng, Fanqiang
Highlights: TG-DTG-MS was equipped to analyze co-pyrolysis characteristics and gaseous productions of MSS and hazelnut shell blend. The activation energy was obtained by three iso-conversional methods and Satava–Sestak method was used to determine mechanism function G(α). Lorentzian function was used to simulate multi-peaks curves and evaluate simulation accuracy. Abstract: Hazelnut shell, as novel biomass, has lower ash content and abundant hydrocarbon, which can be utilized resourcefully with municipal sewage sludge (MSS) by co-pyrolyisis to decrease total content of pollution. The co-pyrolysis of MSS and hazelnut shell blend was analyzed by a method of multi-heating rates and different blend ratios with TG-DTG-MS under N2 atmosphere. The apparent activation energy of co-pyrolysis was calculated by three iso-conversional methods. Satava–Sestak method was used to determine mechanism function G(α) of co-pyrolysis, and Lorentzian function was used to simulate multi-peaks curves. The results showed there were four thermal decomposition stages, and the biomass were cracked and evolved at different temperature ranges. The apparent activation energy increased from 123.99 to 608.15 kJ/mol. The reaction mechanism of co-pyrolysis is random nucleation and nuclei growth. The apparent activation energy and mechanism function afford a theoretical groundwork for co-pyrolysis technology.